2013
DOI: 10.3390/biology2010040
|View full text |Cite
|
Sign up to set email alerts
|

BRCA1 and Its Network of Interacting Partners

Abstract: BRCA1 is a large multi-domain protein with a pivotal role in maintaining genome stability and cell cycle progression. Germline mutations in the BRCA1 gene confer an estimated lifetime risk of 60%–80% for breast cancer and 15%–60% for ovarian cancer. Many of the germline mutations associated with cancer development are concentrated in the amino terminal RING domain and the carboxyl terminal BRCT motifs of BRCA1, which are the most well-characterized regions of the protein. The function of BRCA1 in DNA repair, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
52
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(55 citation statements)
references
References 107 publications
(238 reference statements)
1
52
0
2
Order By: Relevance
“…It is now clear that the BRcA1 and BRcA2 proteins co-localize with RAd51 complexes on mitotic and meiotic chromosomes following exposure to ionizing radiation or hydroxyurea (7,29). certain other proteins have been reported to interact with BRcA1, including ataxia telangiectasia mutated (ATM)/ATM-related kinase, checkpoint kinase 2, and aurora A protein kinase, to regulate cell cycle progression (30). In the present study, three genes (NF1, SYCP2 and TP53) were found to be associated with BRCA1 in breast cancer and ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%
“…It is now clear that the BRcA1 and BRcA2 proteins co-localize with RAd51 complexes on mitotic and meiotic chromosomes following exposure to ionizing radiation or hydroxyurea (7,29). certain other proteins have been reported to interact with BRcA1, including ataxia telangiectasia mutated (ATM)/ATM-related kinase, checkpoint kinase 2, and aurora A protein kinase, to regulate cell cycle progression (30). In the present study, three genes (NF1, SYCP2 and TP53) were found to be associated with BRCA1 in breast cancer and ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we propose that in Wwox-sufficient cells, Wwox binds Brca1, directly or indirectly, along this central region, competing with other Brca1-interacting proteins critical for promoting HDR. One candidate, Rad50, a component of the MRN complex, binds Brca1 at aa 341–758 32 . This interaction is responsible for stimulating nuclease activity of CtIP and MRN to enable end-resection, which commits cells to HDR or SSA.…”
Section: Discussionmentioning
confidence: 99%
“…Following signal transmission in S/G2 phase, ctlp dissociates from BRCA1 and associates with MRN complex where it exclusively facilitates DNA end-resection and retention of MRN complex at DNA damage site [26][27][28][29][30] . However, BRCA1 (N-terminal, 341-748 amino acids) directly associates with MRN complex via RAD50 component.…”
Section: Association Of Brca1 With Mrn Complex and Resection Of Damagmentioning
confidence: 99%
“…However, BRCA1 (N-terminal, 341-748 amino acids) directly associates with MRN complex via RAD50 component. Earlier, it was only reported that BRCA1-MRN complex remain intact throughout HDR repair and very soon it was found that this process is partly dependent on ATM/ATR mediated hyper-phosphorylation of BRCA1 and CHK2 activation 26,28 . To initiate HDR repair, damaged double strand DNA ends are resected by MRN complex to expose ssDNA ends 5,22 .…”
Section: Association Of Brca1 With Mrn Complex and Resection Of Damagmentioning
confidence: 99%
See 1 more Smart Citation